CD44/Folate Dual Targeting Receptor Reductive Response PLGA-Based Micelles for Cancer Therapy - Zhang, Ru; Jiang, Yunying; Hao, Linkun; Yang, Yang; Gao, Ying; Zhang, Ningning; Zhang, Xuecheng; Song, Yimin (Frontiers in Pharmacology, 2022)
In this study, a novel poly (lactic-co-glycolic acid) (PLGA) -based micelle was synthesized, which could improve the therapeutic effect of antitumor drug Doxorubicin hydrochloride (DOX) and reduce its toxic and side effects. The efficient delivery of DOX was achieved by active targeting mediated by double receptors and stimulating the reduction potential in tumor cells. FA-HA-SS-PLGA polymer was synthesized by amidation reaction, and then DOX loaded micelles were prepared by dialysis method. The corresponding surface method was used to optimize the experimental design. DOX/FA-HA-SS-PLGA micelles with high drug loading rate and encapsulation efficiency were prepared. The results of hydrophilic experiment, critical micelle concentration determination and hemolysis test all showed that DOX/FA-HA-SS-PLGA micelles had good physicochemical properties and biocompatibility. In addition, both in vitro reduction stimulus response experiment and in vitro release experiment showed that DOX/FA-HA-SS-PLGA micelles had reduction sensitivity. Molecular docking experiments showed that it can bind to the target protein. More importantly, in vitro cytology studies, human breast cancer cells (MCF-7), human non-small cell lung cancer cells (A549), and mouse colon cancer cells (CT26) were used to demonstrate that the dual receptor-mediated endocytosis pathway resulted in stronger cytotoxicity to tumor cells and more significant apoptosis. In vivo antitumor experiment, tumor bearing nude mice were used to further confirm that the micelles with double targeting ligands had better antitumor effect and lower toxicity. These experimental results showed that DOX/FA-HA-SS-PLGA micelles have the potential to be used as chemotherapeutic drugs for precise tumor treatment.